Replacing batteries with water by an innovative evaporative cooling process for vehicle air conditioning. Issue 1 (1st November 2022) - Morselli, Nicolò; Cossu, Michele; Muscio, Alberto
Abstract: In plug-in hybrid and battery electric vehicles, the air conditioning system can absorb a significant fraction of the energy stored onboard in the battery pack, thus causing a decrease of the range, or the need of additional battery capacity with its associated mass and cost. An alternative to standard air conditioning systems is provided by evaporative cooling. This was used at the dawn of the automotive industry in the form of direct evaporative cooling, however it did not take hold due to the high relative humidity induced in the vehicle cabin by the supply of almost saturated air, with the consequent risk of condensation and health issues. In recent times, Maisotsenko developed an innovative indirect evaporative cooling system, in which the air introduced in the conditioned compartment is not humidified and it can also be cooled down to dew point rather than to the wet bulb temperature thanks to the system architecture. Water consumption is relatively low, so the same cooling energy provided by a vapor compression system powered by a given mass fraction of the battery pack can be obtained by evaporating a comparable mass of water. The approach is investigated here by theoretical means, in order to explore its potential and identify possible critical issues.